IDEALISME CONSTITUENDUM MAHKAMAH KONSTITUSI DALAM PENGUJIAN UNDANG-UNDANG TERHADAP UNDANG-UNDANG DASAR - Benediktus Hestu Cipto Handoyo (Arena Hukum, 2021)
AbstractJudicial review is one of the authorities of the Constitutional Court most often exercised. This research examines the background of the establishment of Constitutional Court in Indonesia and the ideal construction of the constituendum for the Constitutional Court in implementing the judicial review. This normative research uses regulatory and conceptual approach. The results showes first, the authority to judicial review should be placed in one institution, namely the Constitutional Court, since the continental tradion of laws and regulations is systematic, hyrarchial and pyramidal in nature. Second, the Consttutional Court’s decisions that are often ignored by the law forming institutions have resulted in the Law annulled by the Court not immediately followed up with the issuance of a replacement law. Third, judicial review should not be limited to the statute being reviewed, because the statute concerned are, more likely, related to the other statutes. And fourth, the Constitutional Court’s decisions should be regarded as constitutional jurisprudence and become  referrences for the theory of constitution in general. AbstrakSalah satu wewenang Mahkamah Konstitusi (MK) yang paling sering dilaksanakan dalam keseharian adalah Pengujian UU terhadap UUD. Penelitian ini menganalisa latar belakang kemunculan MK di Indonesia serta bagaimana konstruksi ideal Constituendum bagi MK dalam melaksanakan pengujian tersebut. Penelitian normatif ini menggunakan pendekatan perundang-undangan dan konseptual. Hasilnya pertama, pengujian peraturan perundang-undangan seharusnya diletakkan dalam satu lembaga, yakni MK sebab tradisi continental peraturan perundang-undangan bersifat sistemik hirarkhis piramidal. Kedua, putusan MK yang sering tidak diindahkan oleh lembaga pembentuk UU mengakibatkan UU yang telah dibatalkan oleh MK tidak segera ditindak lanjuti dengan penerbitan UU pengganti. Ketiga, pengujian UU terhadap UUD seharusnya tidak hanya berhenti pada pengujian terhadap UU yang dimohonkan, karena UU tersebut dapat berhubungan dengan UU lain. Keempat, putusan MK seharusnya menjadi constitutions jurispridence dan menjadi rujukan teori konstitusi pada umumnya.